A PATTERNS OF MASCULINITIES IN DISCOURSE OF REPORTS ASSESSING CONDITION OF POLISH STARTUPS ORGANISATIONS - TOBIASIEWICZ, EDYTA (Society Register, 2021)
The purpose of this article is discourse analysis of masculinity created in reports assessing the current condition of Polish startups. The analysis covered reports published by the Startup Poland foundation from 2015-2019. This text is an attempt to apply the heuristic framework of integrative gender theories to interpret the results of the research, and explain how the discursively masculinity was constructed. Startups as innovative professional structures belonging to the knowledge-based economy model are an example of organizations typical of the information society. Numerous studies report changes (crises) occurring among the practiced male patterns (especially those typical for the countries of the global North). The results of the analysis show that despite these reports, the largest startup organizations striving to produce innovative solutions and using modern solutions, on the discursive surface, are associated with cultural patterns of hegemonic masculinity. Polish startups, on a structural and symbolic dimensions, are a highly masculine spaces. However, due to the practice of achieving hegemony, they (startups) can be interpreted in terms of cooperative or hybrid masculinity.